Impact of artificial intelligence on the management of information technology services in an organization - Villacorta Vidal, Cristhian Aldair (2023)
In the study conducted, a systematic review was carried out to analyze the impact of artificial intelligence (AI) on IT service management in an organization. Several search engines such as SciELO, Scopus, Google Scholar and World Wide Science were used to find relevant papers. The articles found were standardized based on language and year of publication. Based on this review, it was concluded that the incorporating of AI into IT service management has a positive impact on organizations. This is because AI can enhance efficiency, improve the quality of the offered service, reduce costs and facilitate decision-making. However, it was also identified that AI can have negative consequences, such as job losses. The automation of certain tasks can result in the replacement of roles traditionally performed by humans. Additionally, it was mentioned that AI can generate rejection due to its non-human or unfriendly behavior, particularly in customer service areas.